Mirror Therapy and Transcutaneous Electrical Nerve Stimulation for Management of Phantom Limb Pain in Amputees — A Single Blinded Randomized Controlled Trial. (1st April 2015) - Tilak, Merlyn; Isaac, Serin Anna; Fletcher, Jebaraj; Vasanthan, Lenny Thinagaran; Subbaiah, Rajalakshmi Sankaran; Babu, Andrew; Bhide, Rohit; Tharion, George
Abstract: Background and Purpose: Phantom limb pain (PLP) can be disabling for nearly two thirds of amputees. Hence, there is a need to find an effective and inexpensive treatment that can be self administered. Among the non‐pharmacological treatment for PLP, transcutaneous electrical nerve stimulation (TENS) applied to the contralateral extremity and mirror therapy are two promising options. However, there are no studies to compare the two treatments. The purpose of this study is to evaluate and compare mirror therapy and TENS in the management of PLP in subjects with amputation. Methods: The study was an assessor blinded randomized controlled trial conducted at Physiotherapy Gymnasium of Physical Medicine and Rehabilitation Department, Christian Medical College, Vellore. Twenty‐six subjects with PLP consented to participate. An initial assessment of pain using visual analogue scale (VAS) and universal pain score (UPS) was performed by a therapist blinded to the treatment given. Random allocation into Group I‐mirror therapy and Group II‐TENS was carried out. After 4 days of treatment, pain was re‐assessed by the same therapist. The mean difference in Pre and Post values were compared among the groups. The change in pre–post score was analyzed using the paired t test. Results: Participants of Group I had significant decrease in pain [VAS (  p  = 0.003) and UPS (  p  = 0.001)]. Group II also showed a significant reduction in pain [VAS (  p  = 0.003) and UPS (  p  = 0.002)]. However, no difference was observed between the two groups [VAS (  p  = 0.223 and UPS (  p  = 0.956)]. Discussion: Both Mirror Therapy and TENS were found to be effective in pain reduction on a short‐term basis. However, no difference between the two groups was found. Substantiation with long‐term follow‐up is essential to find its long‐term effectiveness. Copyright © 2015 John Wiley & Sons, Ltd.